Effect of hormonal and copper IUDs on genital microbial colonisation and clinical outcomes in North-Western Nigeria - Saidu, Abdulhadi D.; Tunau, Karima A.; Panti, Abubakar A.; Nwobodo, Emmanuel I.; Mohammed, Yahaya; Amin, Jamila; Garba, Jamila A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine devices are one of the popular long term reversible contraceptive methods. Earlier forms were associated with genital infections, however more recent types such copper IUDs and hormonal types have been shown to have better safety profile. However, there is no conclusive evidence to demonstrate that hormonal IUD is less associated with genital infection when compared with copper IUDs. The objectives include determination of prevalence of genital tract infections among IUD users, to determine the type of IUD that is less associated with genital infection, and also determine clinical features seen among IUD users. Methods: We conducted a descriptive, cross sectional study of clients who were at 6 months following IUD insertion. Endocervical and high vaginal samples were taken to isolate microbes. Results: The prevalence of genital tract infection was 20% in Copper IUD users and 8.6% among LNG-IUS users. Genital infection was significantly higher among copper IUD users compared to hormonal IUD users (p=0.038, OR= 2.88). Abnormal vaginal discharge was the commonest symptoms among IUD users and formal education was associated with less risk of genital infections (p=0.048). Conclusions: Hormonal IUDs are less associated with genital tract infection compared to copper IUDs and women with formal education are less likely to have genital infection among IUD users.